Towards a comprehensive framework for simulation-based design validation of vehicle systems. (6th December 2012) - Kokkolaras, M.; Hulbert, G.; Papalambros, P.; Mourelatos, Z.; Yang, R.J.; Brudnak, M.; Gorsich, D.
We present an overview of our most recent and ongoing research efforts to develop a comprehensive framework for simulation-based design validation of vehicle systems. Specifically, we present the three major building blocks of our framework: (1) the introduction of an appropriate validation metric for dealing with the multivariate functional data that are the output of dynamic vehicle systems; (2) the robust implementation of a Bayesian interval-based hypothesis testing technique for quantifying the confidence in simulation models used for design under uncertainty; (3) the development of a sequential design optimisation and calibration-based validation methodology that addresses the inadequacy of current validation practices in simulation-based design optimisation. We present a simple yet illustrative example and discuss the techniques being developed currently that will complete the proposed framework.